Evaluación del portafolio de proyectos en el Departamento de Infraestructura Aeronáutica de la Dirección General de Aviación Civil - Cordero-Calderón, Juan Carlos (Instituto Tecnológico de Costa Rica, 2014)
Project portafolio management, area of recent development, aims to manage multiple projects of an organization employing a strategic perspective that allows generating maximum benefit and achieving the execution of the organization´s strategc framework. It must notbe confused with the professional management of projects or programs, although there are similarities. In the present investigation, it is developes an analysis of the portafolio at the Department of Aviation Infraestructure, from the Dirección General de Aviación Civil, DGAC (for its acronym in spanish). In order to set the context of the study, first it is displayed an introduction of the institution and the department as well as its strategic framework. Then, its follows the theoretical framework underlying the analysis. Subsequently, it is included the theory about project portafolio management, the selected methodology and specific aspects of aviation infraestructure projects. Based on the stablished procedures, the next steps of the identification, validation and priorization of the strategic objectives of the department were completed. Then, projects and drafted projects are also validated and prioritized to define the list of candidates fot the portafolio. Finally, several scenarios of combinations of projects are considered to help identify the characteristics of an optimal proposal for project portafolio. The results show that the most important strategic objective corresponds to improvements in international airports, because they handle almost all passenger transport and freight and therefore generate most of the income of the DGAC aeronautical services. Second are the improvements in air side of local airfields, then the development of new airports and finally the improvements in the landward sode of local airfields. These results will be used by the evaluation of projects to calcilate the contribution of each project to the implementation of the corporate strategy and define the most efficient portafolio. It is intended that the rsults serve as useful input for managers to achive the development of aviation in Costa Rica and take most possible advantage of available resorces to meet the economic, social, political and enviromental development target in the country.

Avantica Technologies es una empresa costarricense de desarrollo de software con más de 20 años de experiencia. La mayoría de sus proyectos se ejecutan bajo un ciclo de vida ágil, específicamente Scrum, para aprovechar que esta metodología se adapta mejor al constante cambio y el ambiente altamente competitivo que caracteriza a la industria del software. La empresa ha identificado una serie de problemas relacionados con la calidad que disminuyen su ventaja competitiva, el rendimiento de los proyectos que ejecuta e impactan negativamente la satisfacción del cliente: alto porcentaje de retrabajo, baja productividad, pérdida de confianza en la calidad de los productos de software, altos porcentajes de defectos, sobrecostos, entre otros. El objetivo principal de esta investigación es proponer una metodología de gestión de la calidad que apoye la administración de proyectos de software en Avantica Technologies permitiendo, desde una perspectiva preventiva, mejorar la calidad de los procesos y productos de software. Para lograr dicho objetivo, se realizó un análisis de la situación actual de la empresa con la finalidad de identificar los principales problemas, brechas y defectos relacionados con la calidad. Para esto se realizaron entrevistas, encuestas y grupos focales con colaboradores clave de la empresa y se complementó con un análisis de los activos de los procesos de la organización, revisión documental y observación. Posteriormente, se diseñó una metodología de gestión de la calidad enmarcado en el contexto de la empresa, las recomendaciones de la guía PMBOK, Scrum, las buenas prácticas de la ingeniería de software y la mejora continua. Esta metodología la componen una serie de procesos, políticas, procedimientos y plantillas que apoyan y facilitan la aplicación de la misma en los proyectos que ejecuta la empresa. Finalmente se propone una estrategia, progresiva e incremental, para implementar la metodología de gestión de la calidad en Avantica Technologies, tomando en consideración su cultura organizacional.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos, 2014.
Keywords: Administración de proyectos; Proyectos; Cartera; Aviación; Aeropuertos; Infraestructura